PENGARUH KECERDASAN EMOSIONAL, KOMITMEN ORGANISASIONAL DAN REWARD TERHADAP KINERJA MUTHAWWIF (Studi kasus pada Biro Perjalanan Haji dan Umrah XYZ) - Novri, Ferdy; Rivai, Harif Amali (Sekolah Tinggi Ilmu Ekonomi Semarang, 2019)
This study shows a research about employee performance. This study was designed to observe the correlation between of emotional inteligence, organizational commitment and reward toward employee (muthawwif) performance in al Azhar Islamic Tour in West Sumatra and Riau province. Population of this study was all employees in those regions. There were 65 employees. The data was design as a questionnaire based and analyzed by using SPSS 17.0. The result of the study was the emotional inteligence had significant positive correlation, the organizational commitment had not significant negative correlation and the reward had not significant positive correlation. The implication toward the company needs to give attention their employees (muthawwif) because if we see it from the emotional inteligence side, they have been good due to their Islamic education background. But, there were some problems in organisational commitment and reward which is generally came from the company management system. It will provide affects to the performance.